Foreign Exchange Market Efficiency Tests in Sub-Saharan Africa. - Aron, J; Ayogu, M (1997)
Are frequents in freely floating exchange rates attributable to stabilising speculation reflecting changes in the fundamental determinants of currencies or to destabilising behaviour of various kinds, driving prices away from fundamentals, and creating 'excess' volatility? This paper, motivated by the need to assess appropriate tests for efficiency for the growing range of liberalised and liberalising foreign exchange markets in Sub-Saharan African countries, has the following objectives: (i) briefly to survey the empirical methodology for testing market efficiency in the forex market, with an emphasis on integrating the new cointegration methodology; (ii) highlighting the significant data difficulties in empirical work, given controls and frequent structural breaks, for the use of these techniques in Africa; (iii) illustrating the way in which some of these techniques can be applied in South Africa and some other African countries; and (iv) suggesting further research on efficiency that could be carried out using similar data.